Analytic Hierarchy Process Approach for Selecting Audit Team to Reduce Audit Report Lag - Arafat, Yaumal; Novani, Santi (Yayasan Sinergi Kawula Muda, 2025)
Customs and Excise Audit is the authority held by the Directorate General of Customs and Excise (DGCE) in accordance with 125/PMK.04/2007 concerning Customs Audits. West Java's DGCE (one that has that function) has nine audit teams and aims to complete 42 audit reports in 2023. In mid-October 2023, this office received a non-regular audit assignment of seven auditees and had to select a team that could be assigned from a total of nine audit teams. The average audit completion time from 2017 to mid-2023 has always increased. Audits ideally finish within three months of assignment, as per Minister of Finance Regulation No. 125/PMK.04/2007, Article 12, paragraph (1). The author uses the Analytic Hierarchy Process (AHP) method in the decision-making process to determine seven audit teams with the smallest potential for audit report lag. Collaboration with experts and previous research results are also used to determine the criteria in the process. Notably, the identification of audit teams 1 and 5 as having the highest potential for audit report lag, based on criteria derived from expert collaboration and previous research, was empirically validated. Both teams, when assigned audits under real-world conditions, produced reports with completion times exceeding the average, underscoring the predictive validity of the study's methodology.